Time resolved DCE-MRI of the kidneys: Evaluation of the renal vasculatures and tumors using F-DISCO with and without compressed sensing in normal and wide-bore 3T systems. Issue 31 (5th August 2022) - Yamada, Takahiro; Masui, Takayuki; Sasaki, Masako; Katayama, Motoyuki; Iwadate, Yuji; Takei, Naoyuki; Miyoshi, Mitsuharu
Abstract : Dynamic contrast-enhanced MR imaging (DCE-MRI) has been widely used for the evaluation of renal arteries. This method is also useful for tumor and renal parenchyma characterization. The very fast MRI may provide stable and precise information regarding vasculature and soft tissues. The purpose of this study was to evaluate the ability of DCE-MRI to assess renal vasculatures and tumor perfusions using Differential subsampling with Cartesian ordering with spectrally selected inversion recovery with adiabatic pulses (F-DISCO) with and without compressed sensing (CS) in normal and wide-bore 3T systems. Fifty-one patients who underwent DCE-MRI using F-DISCO with or without CS for evaluation of renal or adrenal regions were included. Image quality, artifacts, fat saturation, and selective visual recognition of renal vasculatures were assessed by using a 5-point scale. Tumor recognition was verified by using a 5-point scale of confidence level. Signal intensities of each structure were also measured. In all cases, the temporal resolution of each phase for DCE-MRI was 1.9 to 2.0 seconds. Image quality, artifacts, fat saturation, and selective visual recognition of vasculatures were all acceptable (mean score 4.2–4.9). The selective visualization of renal arteries and veins was successfully accomplished (mean score 4.0–4.9). Contrast media perfusion for renal vasculature, renal parenchyma, and tumors was also recognized. DCE-MRI for the evaluation of renal vasculatures and tumors using F-DISCO with or without CS can be performed with high temporal and spatial resolutions in normal and wide-bore 3T systems. This information can be obtained in a stable fashion throughout the dynamic contrast study. CS can additionally provide benefits that the total imaging time may be shorter than without CS.